A7.22 Effects of whole-body vibration exercise on physical capacity and prostaglandin metabolites in patients with sporadic inclusion body myositis. (24th February 2016) - Korotkova, M; Sandström, S; Hallén, A; Idborg, H; Dorph, C; Alexanderson, H
Abstract : Background: Sporadic inclusion body myositis (sIBM) is a rare condition with slow progression of muscle weakness and muscle atrophy leading to severe disability. Knowledge of exercise effects in sIBM is limited. Objective: To evaluate the effects of whole-body vibration (WBV) exercise on physical capacity, disease activity and urine levels of prostaglandin metabolites (PG-M) in patients with sIBM. Methods: A single subject experimental design was used including four males with sIBM (aged 67–73, diagnosis duration 3–7 years). All were ambulant. During a 6-week non-interventional A-phase participants (P) were assessed every other week; muscle strength (hand-held myometer), physical capacity (30-metre walking test, Sit-to-stand test, heel-lift test), disease activity (6-item core set; physician/patient global, Manual Muscle test, Health Assessment Questionnaire, CK-levels, extra-muscular scores) and urine PG-M levels as an index of systemic PG production. Urine PG-M levels were analysed using LC-MS/MS. During the 12 week interventional B-phase P exercised four muscle groups in upper/lower extremities twice a week. Assessments continued every other week. Intensity started on 30 Hertz (Hz) in two 30-sec sets, increasing up to 45 Hz, 300-sec sets, 4 sets per muscle group. Two consecutive B-phase assessments above/below the A-phase mean + 2SD represented a statistically significant change. Reduced disease activity was defined according to international consensus; >20% improvement in 3/6 items with worsening >25% in no more than 2 items. Results: P1 experienced the exercise as uncomfortable and stopped after eight weeks and remained unchanged. P2 improved significantly in heel-lift repetitions (A-phase mean 60.3+2SD 27, 4 consecutive B-phase assessments between 100–109), in 30-metre walk time (16.2 + 1.5, 5 between 14.3 – 13.7 s) and had reduced disease activity. P3 improved in sit-to-stand repetitions (10 + 1.5, 3 between 13 – 16). P4 improved in sit-to-stand repetitions (10 + 1.5, 5 between 14 – 18) and in knee extensor strength (36.7 + 3.5, 2 between 48–52 Newton). No changes in systemic production of PGE2 and PGD2 or CK-levels were observed in response to exercise. Conclusions: The WBV exercise resulted in improved physical capacity. This program was safe with stable prostaglandin and CK levels throughout the study. One P even had reduced disease activity.